WAIS Divide Ice Core Electrical Conductance Measurements, Antarctica - Fudge, T. J.; Taylor, Kendrick C. (IEDA: US Antarctic Program Data Center, 2014)
Abstract: This data set contains electrical measurements that were used to develop the WDC06A-7 timescale.